Prediction of rowing performance from anthropometric and metabolic variables in lightweight and heavyweight male rowers - Maeestu, J. (University of Tartu, Faculty of Exercise and Sport Sciences Institute of Sport Pedagogy, 2001)
According to the review of the literature, rowing performance is determined by several anthropometric and metabolic factors. However, limited information is available on the relationships between different anthropometric parameters, metabolic variables and rowing performance in male lightweight and heavyweight sculling rowers. The aim of this study was to examine the possible contribution of different anthropometric and metabolic indices to rowing ergometer performance in male lightweight and heavyweight sculling rowers. The purposes of this study were to: 1.measure different anthropometric and metabolic variables in male sculling rowers; 2.compare various methods and criteria used to identify anaerobic threshold in male sculling rowers and find the best indicator of rowing performance from identified different concepts of anaerobic threshold; 3.develop performance prediction models to predict rowing performance in lightweight male sculling rowers using different anthropometric and metabolic variables; and 4.develop performance prediction models to predict rowing performance in heavyweight male sculling rowers using different anthropometric and metabolic variables.